Strong Anisotropic Rashba Effect with Tunable Spin-Splitting in Two-Dimensional Janus Vanadium Dichalcogenides Monolayer - Affandi, Yusuf; Absor, Moh. Adhib Ulil; Anshory, Muhammad; Amalia, Wardah (Universitas Gadjah Mada, 2024)
Motivated by the recent discovery of the Rashba effect in two-dimensional (2D) Janus Transition Metal Dichalcogenides (TMDs) systems, we explore the Rashba effect on the Janus VXY (X = S, Se, Y = Se, Te) monolayer. By employing first-principles density functional theory (DFT) calculations, we find a strong anisotropic Rashba splitting observed around Γ points in the first Brillouin zone. We analyze this anisotropy of Rashba splitting by using k·p perturbation theory synergized with group symmetry analysis. By giving the effect of the biaxial strain, we manipulate the characteristics of the Rashba splitting on the Janus Vanadium Dichalcogenides system. Through spin texture analysis, we reveal both the in-plane and out-of-plane components of the spin textures, providing further evidence for the anisotropic nature of the Rashba spin-orbit coupling (SOC). The observed tuneable Rashba splitting by applying the strain effect shows that the Janus Vanadium dichalcogenides system has the potential to be used as a semiconductor material for spintronic devices.